How Do Mass Shootings Affect Community Wellbeing? - Aparna Soni; Erdal Tekin (Institute of Labor Economics (IZA), 2020)
Over the past four decades, more than 2,300 people have been the victims of mass shootings involving a firearm in the United States. Research shows that mass shootings have significant detrimental effects on the direct victims and their families. However, relatively little is known about the extent to which the impacts of these tragedies are transmitted into communities where they occur, and how they influence people beyond those directly affected. This study uses nationally representative data from the Gallup-Healthways survey to assess the spillover effects of mass shootings on community wellbeing and emotional health outcomes that capture community satisfaction, sense of safety, and levels of stress and worry. We leverage differences in the timing of mass shooting events across counties between 2008 and 2017. We find that mass shootings reduce both community wellbeing and emotional health. According to our results, a mass shooting is associated with a 27 percentage point decline in the likelihood of having excellent community wellbeing and a 13 percentage point decline in the likelihood of having excellent emotional health four weeks following the incident. The effects are stronger and longer lasting among individuals exposed to deadlier mass shootings. Furthermore, the reductions in wellbeing are greater for parents with children below age 18. Our findings suggest that mass shootings have significant societal costs and create negative spillover effects that extend beyond those immediately exposed.
Keywords: I12; I18; K42; 330; mass shooting; gun; crime; violence; happiness; wellbeing; mental health; depression; homicide